NILAI-NILAI PENDIDIKAN DALAM KITAB AL BARJANJI PENGARUHNYA TERHADAP KARAKTER RELIGIUS DI SISWA MTS DARUL HIKMAH - moh ichsan zaelani; Nur Taufik Hidayat (STAI Sebelas April Sumedang, 2021)
The background of the author conducting this research stems from problems that are often encountered at the research location, namely the individual behavior of each MTs Darul Hikmah student. Is there any influence of habituation of reading Al Barjanji on the religious character of MTs Darul Hikmah students? Then this study aims to find out the educational values in the book of Al Barjanji its influence on the religious characteristics of MTs Darul Hikmah students. The research method that the author did here is to use a quantitative approach which is a correlational survey research, which is research carried out aimed at determining the level of relationship between dependent variables and independent variables. The relationship between one and another variable is expressed by the magnitude of the correlation coefficient and meaningfulness (significance).The results showed that the Educational Values in the book of Al Barjanji in the good category were 67.4% because they were in the interval of 61-80%. Religious Characteristics of MTs Darul Hikmah Students are classified in the good category of 67.4 at intervals of 61-80%. Thus, it can be concluded that the more often students read Al Barjanji, the more the religious character of MTs students darul Hikmah will increase.